2012
DOI: 10.1038/srep00816
|View full text |Cite
|
Sign up to set email alerts
|

Surface-plasmon-enhanced deep-UV light emitting diodes based on AlGaN multi-quantum wells

Abstract: We report the development of complete structural AlGaN-based deep-ultraviolet light-emitting diodes with an aluminum thin layer for increasing light extraction efficiency. A 217% enhancement in peak photoluminescence intensity at 294 nm is observed. Cathodoluminescence measurement demonstrates that the internal quantum efficiency of the deep-UV LEDs coated with Al layer is not enhanced. The emission enhancement of deep-UV LEDs is attributed to the higher LEE by the surface plasmon-transverse magnetic wave coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 53 publications
2
80
0
Order By: Relevance
“…Huang et al demonstrated for the first time that the enhanced emission of DUV-LEDs coupled to LSPRs generated by Al nanoparticles prepared on quantum wells (QWs) [66,67]. Size-and density-controlled Al nanoparticles were fabricated by OAD (see Sect.…”
Section: Duv-ledsmentioning
confidence: 99%
“…Huang et al demonstrated for the first time that the enhanced emission of DUV-LEDs coupled to LSPRs generated by Al nanoparticles prepared on quantum wells (QWs) [66,67]. Size-and density-controlled Al nanoparticles were fabricated by OAD (see Sect.…”
Section: Duv-ledsmentioning
confidence: 99%
“…Recently, the LEE of NUV-LEDs is expected to be enhanced by the LSPs and TM-light coupling. At a LSPs-TM light resonance condition, it provides that metallic nanoparticles capture the trapped TM-light in p-GaN layer and transparent conductive layer of LED device and enhance the extracting efficiency of light [27,28]. In this case, the energy of the generated photons in the active layers is first transferred to the metallic nanoparticles to induce LSPs followed by emission of light.…”
Section: Introductionmentioning
confidence: 97%
“…Group III nitrides, such as AlN and AlGaN, have attracted great attention due to increasing demand for ultraviolet light sources used in various applications [1][2][3][4]. Low dislocation densities are needed to improve device performance, as dislocations usually act as nonradiative recombination centers [5].…”
Section: Introductionmentioning
confidence: 99%